Morphological and histochemical study of the myotomal muscle in pacu (Piaractus mesopotamicus Holmberg, 1887) during the initia growth phases - Dal Pai-Silva, Maeli [UNESP]; Silva Freitas, Erika Maria [UNESP]; Dal Pai, Vitalino; de Castro Rodrigues, Antônio [UNESP] (My University, 2003)
Morphological and histochemical methods were used to evaluate the myotomal muscle characteristics of pacu (Piaractus mesopotamicus) from hatching to 40 days old. During the larval period, the musculature consisted predominantly of white muscle. White and red muscle mass increased at 10, 20, 30 and 40 days after hatching. The larvae had round muscle fibers with a moderate degree of maturation and central nuclei. In subsequent phases, small and immature fibers were visible near larger and more differentiated fibers. Undifferentiated cells or presumptive myoblast located in embryogenic zones were visible in the dorsal and ventral regions, and were more evident at 30 and 40 days. The red muscle fibers located in the subdermal region, had oxidative metabolism and slow contraction, whereas the more predominant white muscle fibers had glycolytic metabolism and fast contraction. Our findings indicate that during the initial phases, myotomal muscle growth in pacu occurs by both, muscle fiber hypertrophy and hyperplasia. The analysis of frequency of red and white muscle fibers shows that hyperplastic growth is intense in this period. As the growth rate in adult fish is related to the number of muscle fibers in young fish, extrinsic factors could change the muscle fiber phenotype and influence their ultimate size.